(untitled) (Praxis Educativa, 2023)
The crisis generated by the Covid-19 pandemic forced the organization of non-face-to-face educational alternatives; a situation that in Technical Education affected one of its central axes: learning from practice. This forced the generation of new strategies to sustain the activities of workshops and professionalizing practices. This article aims to examine how previous and emerging inequalities, linked to territorial heterogeneities, to the governance of the system and to the implementation of practices, configured different scenarios for the deployment of policies and strategies at the level of jurisdictions during the pandemic crisis. Based on an investigation focused on the testimonies of jurisdictional referents ofTechnical and Vocational Education and on secondary descriptive data, different regions ofthe country are contrasted. The article shows the way in which the aforementioned heterogeneities are themselves the conditions of possibility to face the pandemic crisis and, therefore, the capacity to mitigate or not, its effects on the continuity of education.